Pengembangan Buku SMA Biologi Kelas XI Semester Ganjil Berbasis Kasus untuk Meningkatkan HOTs - Lasrini Lasrini; Martina Restuati; Hasruddin Hasruddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to improve students' High Order Thinking Skills (HOTs) in high school biology by developing a case-based biology textbook. The research method used is the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation. Data collection involved feasibility testing, practicality testing, and effectiveness testing. The results showed that the case-based biology textbook obtained a feasibility score of 95.8%, a practicality score of 95.5%, and an effectiveness score with an n-gain of 0.46 (moderate category). In conclusion, the developed case-based biology textbook is considered feasible, practical, and effective in enhancing high school students' HOTs. Keywords: ADDIE, Textbook, HOTs, Case, Senior High School